2017
DOI: 10.17352/2455-5487.000049
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical Spinal Decompression an Effective Physiotherapy Modality for Neck and Back Pain

Abstract: Background: Non-surgical spinal decompression is a novel physiotherapy that improves on conventional traction by adding computer technology and it is commonly used along with other physiotherapy modalities. Indications include bulging or herniated discs, degenerative disc disease, facet syndrome, sciatica, neck pain and lower back pain. The purpose of this practice-based observational study was to investigate the effectiveness of decompression for patients with radiculopathy or chronic spinal pain that failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In the midst of this controversy, this present research shows a slightly lower mean patients ending pain severity score that were statistically significant despite these patients having reported no improvement with previous interventions (such as medication, routine physiotherapy, surgery). This is in line with previous findings in support of the efficacy of IDD therapy in conjunction with other conventional conservative treatment studies [28,35,[55][56][57]. Although there was no control group used in this research, the authors would argue that it is difficult for a physical intervention to offer a persuasive placebo treatment.…”
Section: Conflicts Of Interestsupporting
confidence: 89%
See 2 more Smart Citations
“…In the midst of this controversy, this present research shows a slightly lower mean patients ending pain severity score that were statistically significant despite these patients having reported no improvement with previous interventions (such as medication, routine physiotherapy, surgery). This is in line with previous findings in support of the efficacy of IDD therapy in conjunction with other conventional conservative treatment studies [28,35,[55][56][57]. Although there was no control group used in this research, the authors would argue that it is difficult for a physical intervention to offer a persuasive placebo treatment.…”
Section: Conflicts Of Interestsupporting
confidence: 89%
“…Nevertheless, the effectiveness of IDDT in the management of chronic LBP has been shown by findings from previous studies [28,35,55,56]. In a retrospective chart audit, it was confirmed that NSD uses DRX9000 and a treatment regimen (lumbar stretching, myofascial rele-…”
Section: Outcome/outcome Measuresmentioning
confidence: 89%
See 1 more Smart Citation
“…Cholewicki et al found in their study minimal activity in truncal muscles after using IDD therapy and supports rehydration theory for the improvement seen in patients undergoing this therapy [18]. There are multiple studies published over the years that showed positive effects of IDD therapy over conventional traction therapy in patients with LBP and cervical pain as well [19][20][21][22]. Amjad F et al conducted a randomized study where one group was given non-surgical decompression along with physical therapy and the other group was given only physical therapy [23].…”
Section: Reviewmentioning
confidence: 79%
“…However, with recent advances, new technology has been developed, i.e. Non-surgical spinal decompression (NSD) therapy is used to overcome the drawbacks of traction and decompressing the spinal nerve roots non-surgically by using a sensitive computerized feedback mechanism [ 9 , 20 , 21 ]. This system is designed to provide a motorized segmental distraction for a specified time [ 22 ] which may induce physical changes to the disc [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%